The Intelligent Control System of the Freezing Station in Coal Mine Freezing Shaft Sinking - Xiaoliang Zheng; Yelin Hu; Zhaoquan Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to address the issue of low degree of automation and huge waste of electric energy of the equipment in drilling engineering freezing station which adopts the freezing method of coal mine, we need to design an intelligent control system to control both the brine pump and double stage ammonia screw compressor. According to the actual cooling need in freezing project, this new system is able to adjust the working condition of the equipment so as to optimize the supply as needed. Also, the temperature and flow of the brine are controlled by fuzzy decoupling controller, and variable frequency controller is adopted in the brine pump to change the motor drive speed and finally adjust the flow of the brine appropriately, besides, the reasonable start-stop unit is used in the compressor to control the temperature of the brine. It has turned out that this intelligent control system features a better control performance, and thus has increased the automation level and prolonged the using life of the whole system as well as saved a large amount of electric energy and decreased the electricity cost of construction enterprises.